2011
DOI: 10.1111/j.1365-2796.2010.02292.x
|View full text |Cite
|
Sign up to set email alerts
|

LDL-associated apolipoprotein J and lysozyme are associated with atherogenic properties of LDL found in type 2 diabetes and the metabolic syndrome

Abstract: Objectives. Exchangeable low-density lipoprotein (LDL)-associated proteins can affect the atherogenic properties of LDL. Our aim was to analyse the protein composition of LDL from individuals with or without type 2 diabetes and the metabolic syndrome (T2DM) in relation to other LDL particle characteristics, to assess whether certain proteins associate more with certain subclasses of LDL typical for T2DM, such as small, apoCIII-rich LDL.Design. Low-density lipoprotein from two cohorts of 61-year-old men (n = 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…The content of apoJ in lipoproteins is altered in patients with coronary heart disease or with CVR factors, including obesity, insulin resistance and dyslipidemia [13,14,29,32]. It has been shown that a low content of apoJ in HDL may compromise the anti-apoptotic function of this lipoprotein in patients with coronary heart disease [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of apoJ in lipoproteins is altered in patients with coronary heart disease or with CVR factors, including obesity, insulin resistance and dyslipidemia [13,14,29,32]. It has been shown that a low content of apoJ in HDL may compromise the anti-apoptotic function of this lipoprotein in patients with coronary heart disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…HDL proteome remodeling in CAD, in particular increased apoC-III and decreased apoJ content, impairs the activation of endothelial antiapoptotic pathways [13]. Other authors have reported that apoJ content in LDL is increased in diabetic patients [29]. These findings suggest that the distribution of apoJ is abnormal in subjects with high CVR.…”
Section: Introductionmentioning
confidence: 96%
“…Although all proteomic analyses performed in LDL have detected the presence apoJ in this lipoprotein, few studies have investigated the role of apoJ on LDLs. Karlsson et al reported that apoJ is increased in LDLs from obese subjects (54), and Pettersson et al described increased apoJ content in small dense LDLs from patients with diabetes and metabolic syndrome (20). These findings suggest that the low content of apoJ in HDLs in these patients could be caused by an altered distribution of apoJ among the lipoprotein fractions.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the relationship between apoJ and very LDLs or LDLs are scarce, and the role of apoJ in these lipoproteins is virtually unknown. Petterson et al described that, in diabetic patients, the content of apoJ is increased in small dense LDLs (20), an atherogenic form of LDLs related with high CVR. Schwarz et al reported that apoJ binds to LDLs treated with cholesteryl esterase and plasmin [enzymatically modified LDLs (E-LDLs)] (21), inhibiting its cytotoxic capacity.…”
mentioning
confidence: 99%
“…Indeed, commonly known polymorphisms in clusterin gene are positively correlated with the risk of type-II diabetes (T2DM)22. However, there are unclear reports on the correlation between serum clusterin concentration and T2DM232425. Similarly, unclear reports also exist for correlation between levels of clusterin and obesity2526.…”
mentioning
confidence: 99%